2011
DOI: 10.5012/bkcs.2011.32.12.4297
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free Synthesis of Propargylic Alcohols using ZnO as a New and Reusable Catalyst by Direct Addition of Alkynes to Aldehydes

Abstract: Under solvent-free conditions, the synthesis of propargylic alcohols by direct addition of terminal alkynes to aldehydes promoted by ZnO as a novel, commercially, and cheap catalyst is described. Furthermore, the catalyst can be reused for several times without any significant loss of its catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Actually,z inc salts have been reported to act as catalysts for promoting the coupling of terminal alkynes with aldehydes. [8] However,t hese reactions are only able to access propargylic alcohols.A ne xtra oxidation step is required for accessing ynones.Recently,our group found that excess amounts of zinc iodide could mediate the dehydrogenation reaction of the in situ generated propargylic alcohols with an additional amount of aldehyde. [9] However,t he use of al arge excess of zinc salts and aldehydes hindered this protocol from general application.…”
mentioning
confidence: 99%
“…Actually,z inc salts have been reported to act as catalysts for promoting the coupling of terminal alkynes with aldehydes. [8] However,t hese reactions are only able to access propargylic alcohols.A ne xtra oxidation step is required for accessing ynones.Recently,our group found that excess amounts of zinc iodide could mediate the dehydrogenation reaction of the in situ generated propargylic alcohols with an additional amount of aldehyde. [9] However,t he use of al arge excess of zinc salts and aldehydes hindered this protocol from general application.…”
mentioning
confidence: 99%
“…Actually,z inc salts have been reported to act as catalysts for promoting the coupling of terminal alkynes with aldehydes. [8] However,t hese reactions are only able to access propargylic alcohols.A ne xtra oxidation step is required for accessing ynones.Recently,our group found that excess amounts of zinc iodide could mediate the dehydrogenation reaction of the in situ generated propargylic alcohols with an additional amount of aldehyde. [9] However,t he use of al arge excess of zinc salts and aldehydes hindered this protocol from general application.…”
mentioning
confidence: 99%